2022
DOI: 10.3389/frwa.2022.867201
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Personal Care Products, Pharmaceuticals, and Stimulants in Mgeni and Msunduzi Rivers, KwaZulu-Natal, South Africa

Abstract: In this work, environmental occurrence and risk assessment of pharmaceuticals, personal care products (PPCPs), and stimulants are presented. A quantitative technique is described for ultrasonic-assisted solid-phase extraction (SPE) followed by GC-MS after derivatization of PPCPs; propylparaben, triclosan, carbamazepine, chloramphenicol, and stimulant caffeine. Ultrasonic-assisted extraction together with centrifugation were used to extract sediment samples collected from the Mgeni and Msunduzi rivers. An SPE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…35 In fact, some studies have found the concentrations of carbamazepine in surface water to be minimal with its quantities not exceeded the method quantitation limits. 35,37,46,64 This observation could be associated with the transformation of carbamazepine into other compounds as indicated elsewhere. 45 However, some of these studies did not investigate the occurrence of the transformation products in the same samples.…”
Section: Research Articlesupporting
confidence: 56%
See 3 more Smart Citations
“…35 In fact, some studies have found the concentrations of carbamazepine in surface water to be minimal with its quantities not exceeded the method quantitation limits. 35,37,46,64 This observation could be associated with the transformation of carbamazepine into other compounds as indicated elsewhere. 45 However, some of these studies did not investigate the occurrence of the transformation products in the same samples.…”
Section: Research Articlesupporting
confidence: 56%
“…45 Other reported applications for Oasis HLB sorbents include their use in the simultaneous extraction of pharmaceuticals, personal care products and stimulants in aqueous samples. 46 Despite its success in sample preparation, Oasis HLB seems to be more suitable for a wide range of analytes. In this regard, the selectivity concerns become prominent when it is used for fewer analytes with similar physico-chemical properties.…”
Section: Commercially Available Solid-phase Extraction Sorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The averages of the concentration of the veterinary pharmaceuticals (ivermectin, salicylic acid, and tetracycline) in the surface water (Table 4 ) were used as our MEC SW . The MEC can be used in place of the predicted environmental concentration (Gumbi et al, 2022 ). The no observed effect concentration (NOEC) data used in this study were generated using the ToxRat software for 24‐ to 72‐h EC 50 P. subcapitata and 24‐ to 48‐h LC 50 D. magna , but the NOEC for T. thermophila was not calculated from the ToxRat software.…”
Section: Methodsmentioning
confidence: 99%